2017
DOI: 10.1039/c7mh00197e
|View full text |Cite
|
Sign up to set email alerts
|

A new class of chiral semiconductors: chiral-organic-molecule-incorporating organic–inorganic hybrid perovskites

Abstract: Chiral organic–inorganic hybrid perovskites exhibiting circular dichroism were prepared as a new class of chiral semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
435
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 336 publications
(462 citation statements)
references
References 33 publications
25
435
1
1
Order By: Relevance
“…The CD spectra of semiconductor inorganic nanomaterials have been illustrated . However, the resulted g ‐factors (the measure of the strength of the CD signal at a given extinction intensity) of such materials are relatively small and are dependent on colloidal chemistry, which limits the practical device development and indicates the difficulty in fabricating thin films from the nanoparticle‐like morphology and the formation of a dielectric barrier by the organic components . Recent studies revealed that perovskites could provide a platform wherein the inorganic framework could be readily copped with a wide range of chiral components to form chiral perovskite crystals, exhibiting CD signals with strong g ‐factors.…”
Section: Properties Of Chiral Perovskite Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CD spectra of semiconductor inorganic nanomaterials have been illustrated . However, the resulted g ‐factors (the measure of the strength of the CD signal at a given extinction intensity) of such materials are relatively small and are dependent on colloidal chemistry, which limits the practical device development and indicates the difficulty in fabricating thin films from the nanoparticle‐like morphology and the formation of a dielectric barrier by the organic components . Recent studies revealed that perovskites could provide a platform wherein the inorganic framework could be readily copped with a wide range of chiral components to form chiral perovskite crystals, exhibiting CD signals with strong g ‐factors.…”
Section: Properties Of Chiral Perovskite Materialsmentioning
confidence: 99%
“…Recent studies revealed that perovskites could provide a platform wherein the inorganic framework could be readily copped with a wide range of chiral components to form chiral perovskite crystals, exhibiting CD signals with strong g ‐factors. Ahn et al incorporated S ‐ and R ‐MBA into the layered lead iodide perovskite structure and obtained chiral perovskite structure of ( S ‐MBA) 2 PbI 4 and ( R ‐MBA) 2 PbI 4 . The transmission CD spectra, as depicted in Figure a, displayed optical activity located in the region of 350–800 nm, which can be attributed to the incorporation of organic cations.…”
Section: Properties Of Chiral Perovskite Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chirality describes the configuration or handedness (left or right) of an asymmetric material system. Chiral materials have low symmetry but contain two mirror‐image states and they are difficult to distinguish synthetically but can be distinguished geometrically . Chirality transfer is shown in Figure a, where 〈n〉 represents the average number of inorganic layers that are separated by the larger‐scale organic ligands .…”
Section: Various Approaches To Construct Hop Spin‐related Optoelectromentioning
confidence: 99%